(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
Several trends exist while living the world with some extremities: there is a scale from a modern, little superficial, self-serving, belief in the omnipotence of social media philosophy of life till a much deeper concept that guarantees living the experience. It is present in every field of life - so travel is no exception, either. The slow philosophy sensing the spirituality of the place is also gaining ground in tourism - as a kind of counterpoint to modern “Instagram” tourism. The article examines the validity of this concept today and presents a survey conducted among Hungarian respondents. It examines, how important it is for respondents to avoid destinations visited by the masses, to travel in an eco-friendly way or to become a part of the place while sipping on the culture of the place. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.